2012
DOI: 10.1093/pasj/64.6.124
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Near-Infrared Polarimetry of a Circumstellar Disk around UX Tau A

Abstract: We present H-band polarimetric imagery of UX Tau A taken with HiCIAO/AO188 on the Subaru Telescope. UX Tau A has been classified as a pre-transitional disk object, with a gap structure separating its inner and outer disks. Our imagery taken with the 0.15 ′′ (21 AU) radius coronagraphic mask has revealed a strongly polarized circumstellar disk surrounding UX Tau A which extends to 120 AU, at a spatial resolution of 0.1 ′′ (14 AU). It is inclined by 46 • ± 2 • as the west side is nearest.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The radial index of −3 is expected for a vertically flat disk or a disk with a constant opening angle (Whitney & Hartmann 1992;Momose et al 2015). This slope has commonly been observed for protoplanetary disks in Stokes I, and has been found in P I as well (e.g., Tanii et al 2012). Therefore, we propose that the region behind the arc is vertically settled and shadowed by the arc structure.…”
Section: Radial Surface Brightness Distributionsupporting
confidence: 83%
“…The radial index of −3 is expected for a vertically flat disk or a disk with a constant opening angle (Whitney & Hartmann 1992;Momose et al 2015). This slope has commonly been observed for protoplanetary disks in Stokes I, and has been found in P I as well (e.g., Tanii et al 2012). Therefore, we propose that the region behind the arc is vertically settled and shadowed by the arc structure.…”
Section: Radial Surface Brightness Distributionsupporting
confidence: 83%
“…For HD 142527, Canovas et al (2013) derived polarisation fraction of 10%-25% at H-band; however, Avenhaus et al (2014) reported significantly higher polarisation fraction for this object (20%-45%) at H-band. Tanii et al (2012) show that polarisation fraction of UX Tau is up to 66% at H-band. Furthermore, Poteet et al (2018) have shown that polarisation fraction of TW Hya is as high as 63% ± 9%.…”
Section: Comparison With Disc Observationsmentioning
confidence: 86%
“…Instead of bare stellar photospheres, the calibrators used for LkCa 15 in Sallum et al (2015b) and especially Kraus & Ireland (2012) include multiple stars with bright resolved disk emission on the same spatial scale as LkCa 15's disk: some are also highly variable (e.g. GM Aur, UX Tau; Tanii et al 2012;Oh et al 2016b).…”
Section: Discussionmentioning
confidence: 99%